2018
DOI: 10.1039/c8ra04698k
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating Seebeck coefficients in π-stacked molecular junctions

Abstract: When two adjacent molecules are slid across each other, quantum interference causes oscillations in their conductance and Seebeck coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Figure C shows the room‐temperature conductance evolutions during stretching as obtained from the transmission coefficients at the Fermi level estimated by DFT. During junction stretching, oscillations in conductance occur, as theoretically predicted and measured in previous studies, and the conductance histograms (Figure C, inset) suggest that the calculated conductance of dimers is approximately 10 −5.0 G 0 . The similar conductance regions among different derivatives and variation tendency provide qualitative theoretical evidence for the conductance consistency observed experimentally.…”
Section: Resultssupporting
confidence: 85%
“…Figure C shows the room‐temperature conductance evolutions during stretching as obtained from the transmission coefficients at the Fermi level estimated by DFT. During junction stretching, oscillations in conductance occur, as theoretically predicted and measured in previous studies, and the conductance histograms (Figure C, inset) suggest that the calculated conductance of dimers is approximately 10 −5.0 G 0 . The similar conductance regions among different derivatives and variation tendency provide qualitative theoretical evidence for the conductance consistency observed experimentally.…”
Section: Resultssupporting
confidence: 85%
“…Thet ransmission curves demonstrate that both constructive and destructive quantum interference are observed during the stretching process.However,only the high conductance state was obtained in our experiments owing to the relatively high stretching rate,w hich is in accordance with the previous report. [20] Figure 5C shows the room-temperature conductance evolutions during stretching as obtained from the transmission coefficients at the Fermi level estimated by DFT.D uring junction stretching, oscillations in conductance occur, as theoretically predicted [21] and measured [20] in previous studies,a nd the conductance histograms ( Figure 5C,i nset) suggest that the calculated conductance of dimers is approximately 10 À5.0 G 0 .T he similar conductance regions among different derivatives and variation tendency provide qualitative theoretical evidence for the conductance consistencyo bserved experimentally.…”
Section: Resultsmentioning
confidence: 61%
“…To address the problem of increasing the thermoelectric performance of organic molecules, Finch et al 10 demonstrated theoretically that large values of the Seebeck coefficient could be obtained by creating transport resonances and anti-resonances within the HOMO-LUMO gap and tuning their energetic location relative to the Fermi energy. Following these pioneering works, several experimental [11][12][13][14][15][16][17][18][19][20] and theoretical studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34] have attempted to probe and improve the thermoelectric performance of single molecules. However, progress has been hampered by the additional complexity of thermoelectric measurement set-ups, because unlike measurements of single-molecule conductance, Seebeck measurements require additional control and determination of temperature gradients at a molecular scale.…”
Section: Introductionmentioning
confidence: 99%